ANALISIS BENTUK LAGU DAN TEKNIK GARAPAN KOMPOSISI RECUERDOS DE LA ALHAMBRA KARYA FRANSISCO TARREGA - Tri Saputra; Esy Maestro; Yensharti Yensharti (SENDRATASIK UNP, 2016)
The purpose of this study is to describe the composition analysis recuerdos de la Alhambra works of Francisco Tarrega. This research uses a qualitative approach through analysis study (content analysis). Data collection through literature studies and laboratory work. Analysis of the composition Recuerdos de la Alhambra examines the form of songs that includes motifs, phrases, periods and cultivation techniques that include the technique of playing the right hand and left hand playing techniques. The theory used prier theory, Banoe and Poerwadarmita. That said point a is a collection of motifs, phrases, periods and cultivation techniques. The composition of the research results Recerdos de la Alhambra works of Francisco Tarrega consists of a 55-bar using ¾ time signature by using the basic tone C major and modulated to the basic tone of A major. Song form consists of a form that is A (a a '), consists of two motives in the phrase antecedents and motives in the phrase concequens 3. In the arable techniques there are two, namely the technique of the game in the right hand and left hand technique in the game. On the right hand playing techniques there is one bar that uses apoyando and and tirando which include: there are two bars which uses techniques tirando on chords, arpeggios and a 1-bar at 52 bars in tremolo. On the right hand covering: 5 bars on technique slur, 1 time signatures on the slide technique and 8 bars at barre technique.Keywords : Analysis, Forms and Techniques Arable, Composition, Recuerdos De La Alhambra